Molecular characterization of Streptococcus uberis strains, isolated in a longitudinal study from milk of a commercial South African dairy herd. - Petzer, Inge-Marie (University of Pretoria, 2025)
Mini Dissertation (MSc (Production Animal Studies))--University of Pretoria, 2025.